Fertility preservation in an oncology patient who presented with positive human chorionic gonadotropin - Olivia Carpinello, M.D; Alexandra Aserlind, M.D; Frank Chang, M.D; Arthur Sagoskin, M.D; Eric Widra, M.D (Elsevier, 2020)
Objective: To report the case of a woman who presented for fertility preservation before breast cancer treatment who was found to be pregnant with an undesired pregnancy. Design: Case report. Setting: Single infertility practice. Patient: A 28-year-old woman with a new diagnosis of grade 3 invasive ductal carcinoma of the breast was planning to undergo oocyte cryopreservation and was found to be pregnant with an undesired pregnancy. She underwent a medical termination at a gestational age of 5 weeks 4 days. Neither the patient nor her oncology team wished to delay treatment more than was necessary. The physician and patient decided to initiate controlled ovarian hyperstimulation (COH) before her human chorionic gonadotropin (hCG) returned to normal. Intervention(s): COH in the setting of a positive quantitative hCG. Main Outcome Measure(s): Number of metaphase II (MII) oocytes cryopreserved; doses of Gonal-F and Menopur; serum E2, follicle-stimulating hormone, luteinizing hormone, hCG levels. Result(s): COH began 7 days after passing the products of conception. Baseline labs demonstrated hCG at 222 mIU/mL, follicle-stimulating hormone at <0.10 mIU/mL, luteinizing hormone at <1.10 mIU/mL, and E2 at 147 pg/mL. She was started on an antagonist protocol with the use of 150 IU Gonal F and 75 IU Menopur. She was triggered on stimulation day 14 with 5,000 U hCG, and her peak E2 was 5,924 pg/mL. She ultimately had 18 oocytes retrieved, 12 of which were MII, one MI, and five germinal vesicle. All were vitrified. Conclusion(s): COH can be achieved in the setting of low positive hCG levels with subsequent successful oocyte maturation. The threshold for hCG trigger to be ineffective in the setting of a positive hCG has yet to be determined.